Infohumor and media literacy: understanding comedy to understand news - Aguilera García, Inmaculada Concepción (Historia y Comunicación Social, 2023)
Humor is the part of entertainment that seeks complicity with the public through irony. As a trend, infohumor has been manifest for decades in Spain, as in the case of El intermedio. This research sought to find out if its comedy facilitates the understanding of current affairs. A methodology was proposed in three phases: first, four discussion groups with spectators of both sexes and different ages; then, thirteen interviews with professionals from four programs: El intermedio, Todo es mentira, Ese programa del que usted me habla y La resistencia; and third, another six groups by distinction of age and sex. The study revealed that deepening in the media literacy of infohumor would originate not only critical viewers, but also critical citizens.